1994
DOI: 10.1016/s1063-4584(05)80003-2
|View full text |Cite
|
Sign up to set email alerts
|

The predictive role of scintigraphy in radiographic osteoarthritis of the hand

Abstract: Sixty-seven patients with symptomatic knee osteoarthritis (OA) (26 male, 42 female, mean age 62.7 years) have been followed prospectively for a mean of 67.3 months (range 60-72 months). Hand radiographs were obtained at entry and at follow-up. Scintigraphic images of the hands were obtained at entry, and the predictive value of scan abnormalities for subsequent radiographic change was examined. Forty-six of 203 scan-positive joints at entry showed radiographic change, compared with 41 of 2075 scan-negative joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…One scintigraphy study reported high inter-reader reliability (κ=0.61–0.82),49 and one scintigraphy study reported high intrareader reliability (κ=0.84) 39…”
Section: Resultsmentioning
confidence: 99%
“…One scintigraphy study reported high inter-reader reliability (κ=0.61–0.82),49 and one scintigraphy study reported high intrareader reliability (κ=0.84) 39…”
Section: Resultsmentioning
confidence: 99%
“…In the ACL dog model of OA, Brandt et al [6] reported that, at a later stage of the disease, 54 months after OA induction, there was a marked increase in the volume of subchondral bone with active bone formation. Studies in OA of the knee and the hand reported that the scintigraphic abnormalities correlated with the osteocalcin concentration in the synovial fluid, which is a marker of bone formation, and serum osteopontin, a bone matrix protein, were also elevated [21][22][23]. Gevers and Dequeker also showed elevated serum osteocalcin levels in women with hand OA, and elevated osteocalcin in cortical bone explants [24].…”
Section: Correlation Between In Vivo Findings In Animals and Human Oamentioning
confidence: 96%
“…In OA, subchondral bone is characterized by changes that include bone "bruises" and cyst formation (seen with MRI [10,11]) and increased bone turnover (seen by scintigraphy [3,13]). These are all indicative of abnormal bone remodeling.…”
Section: Oa Joint Pathologymentioning
confidence: 99%